Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada PT. Arthawenasakti Gemilang Tangerang - Hia, Era; Purba, Eduard Hotman; Sari, Meri Mayang (Universitas Pendidikan Ganesha, 2024)
The purpose of the research was to determine the influence of leadership style on employee productivity, the influence of motivation on employee productivity, and the influence of leadership style and motivation on employee productivity at PT. Arthawenasakti Gemilang Tangerang. 841 employees of PT. Arthawenasakti Gemilang Tangerang, which is spread across various parts of its production activities, are used as a population in research. The sample used the Slovin formula for 89 employees. Multiple linear regression, classical assumption tests, t-tests, f-tests, and determination coefficients are used for data analysis techniques. The results obtained are to explain that leadership style partially has a negative effect on employee work productivity; in other words, leadership style does not have much effect on employee work productivity at PT. Arthawenasakti Gemilang Tangerang; motivation partially has a significant effect on the work productivity of employees at PT. Arthawenasakti Gemilang Tangerang. Leadership style and motivation simultaneously affect the work productivity of employees at PT. Arthawenasakti Gemilang Tangerang.